Imagine the sound : experimental African American literature after civil rights - Mathes, Carter, 1971- (University of Minnesota Press, 2015)
Contents Introduction: The Acoustics of Unfreedom 1. The Sonic Field of Resistance: Free Jazz and the Horizon of Black Aesthetic Expansion 2. Apocalyptic Soundscapes: Listening to Henry Dumas's Short Fiction 3. Peering into the Maw: Larry Neal's Aesthetic Universe 4. Sonic Futurity in Toni Cade Bambara's The Salt Eaters 5. The Radical Tonality of James Baldwin's Post-Civil Rights Blues Epilogue: Sounding the Long Civil Rights Moment Acknowledgments Notes Index.